The The Exploitation of Laura Edelenyi's Departure: A Study of Social Semiotics in the Deddy Corbuzier Podcast - Tesalonika Hasugian; Patricia Robin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2022)
The diversity of media trends appears on podcast channels channeled through YouTube. Podcasts have been considered a development form of digital radio. One of the famous YouTubers in Indonesia is Deddy Corbuzier, the owner of the YouTube channel